ASQ: SE-3 Application as an Innovation in Helping Stimulate Children’s Growth and Development for Paediatric Physiotherapy Teaching Materials - Naufal, Adnan Faris; Asmarasikha, Aldila Lutfi; Azkia, Anida Fitri (Universitas Muhammadiyah Surakarta, 2025)
Background: Mobile applications are now a solution to the challenges of monitoring children's growth and development, helping in understanding the emotional and behavioural aspects of children. However, a mobile application-based questionnaire management system for physiotherapy is still not available, therefore, the development of the